The impact of empowerment on emotional labour: a conceptual framework - Abdul Aziz, Yuhanis; Samdin, Zaiton (Universiti Putra Malaysia Press, 2012)
This conceptual paper investigated the importance of employee empowerment and its impact on emotional labour in securing success of service delivery. This study advocates that empowerment is essential and also a key factor in the development of service quality and customer satisfaction. It is predicted that employees who are empowered and display suitable positive emotions at work may be able to manage their emotional labour efficiently. Therefore, the major goal of this paper was to develop and propose a conceptual framework on the impact of empowerment and positive emotions on emotional labour. It aimed to help marketers and managements to have a better understanding of empowering front-line employees in the organisation. Accordingly, this study conceptualised the relationships between empowerment, positive emotions, and negative emotions with deep acting, surface acting and expressions of naturally felt emotions. The model was developed based on the extent literature in services marketing, organisational behaviour and services management literature. Meanwhile, structural equation modelling was proposed to analyse the relationships among the predicted antecedents with their outcomes. The paper foresees contribution in services marketing literature as well as hotel management literature on the importance of empowering employee and its impact on emotional labour